INVESTIGATION OF N-POLICY MARKOVIAN QUEUEING SYSTEM WITH DESPONDENT ARRIVALS, RETAINMENT OF RENEGED CUSTOMERS AND CONTROLLABLE ARRIVAL RATES (Journal of Pharmaceutical Negative Results, 2022)
Afinite capacity, finite source, Markovian queueing model with despondent arrivals, retainment of reneged customers and controllable arrival rates is considered. Using this model, a steady-state solution and system characteristics can be obtained. The measures of effectiveness of the queueing model are also derived. Numerical results are given for better understanding and relevant conclusion is presented.